Deconstructing water sensitivity: experiences from global cities. Issue 1 (November 2020) - Mishra, G; Acharya, G; Iyer, M; Doshi, S
Abstract: Cities around the world today are facing common issues of rapid urbanization, varying climatic conditions, and challenging economies, which are known to impact the environment and quality of life. In response, multiple concepts have emerged related to water management practices over the past few decades. One such recently discussed concept is of Water Sensitive Cities, which envisions a place that judiciously uses its existing resources, building resilience for tomorrow by simultaneously ensuring community participation for sustainability. Synonymous with this notion, there exist other overlapping concepts such as Water Sensitive Urban Design, Low Impact Development, Best Management Practices, Green Infrastructure, and the like. This research intends to deconstruct these concepts and their practices through a review of 120 case studies located across different agro-climatic and water-stressed regions globally. These cases were analyzed for their inclination to three thematic components: society, water sensitive urbanism, and technologies. The evidence suggests that there is not a single water sensitive city in the world today. This paper discusses the Utopian nature of this notion and identifies relevant pathways to explore to reach the destined vision of Water Sensitive Cities.